Effect of forming conditions of poly-lactic acid/hydroxyapatite to tensile strength of canine bone fixation plate using full factorial experimental design - Pornpailin Watcharaprapapong (2018)
© The Authors, published by EDP Sciences, 2018. Problems of using metallic bone fixation plates for canine lead to the idea of the replacement with biocomposite materials. In this research, polylactic acid (PLA) blends with hydroxyapatite (HA) powder 5-15% was used as biocomposite material. The specimens were formed by hot compression molding and the experiment in investigating suitable forming condition was based on the 23 full factorials with the center point design of experiment. There are many types of research attempting to develop a prototype of bone fixation plates from a substitute material including forming conditions, in order to obtain the effective bone fixation plate to use. This paper presents the tensile strength for the proposed biocomposite bone fixation plates. After the mechanical testing on various conditions, the tensile strength results ranged from 40 to 60 MPa and it showed that the higher HA ratio had significant effect to the decrease of the tensile strength. This preliminary experiment reveals the tensile strength of forming conditions of PLA/HA composite, which may indicate a direction for improving the better mechanical properties of the bone fixation plates.